Pengaruh Motivasi, Kepuasan Kerja dan Dukungan Organisasi terhadap Kinerja Karyawan PT. XYZ - Rahel Irianti; Innocentius Bernarto (JURNAL ADMINISTRASI BISNIS, 2021)
This research aims to analyze the influence of employee performance in XYZ’s Company, one of the indicators is to see the attendance data. As the attendance data of XYZ’s employees in 2017-2019 has decreased, that phenomenon underlies this research. So, the purpose of this research is to analyze the influence of motivation, job satisfaction, and organizational support on employee performance of XYZ’s Company. This research is quantitative’s type that using survey methods. The data collection in this research is done using questionnaires to the whole employee of XYZ. So sample for this research is a saturated sample. The number of respondents in this research is 40 employees. Partial lease square-structural equation (pls-sem) analysis was conducted using SmartPLS 3.0 program to analyze the data. The result showed that motivation, job satisfaction, and organizational support have a positive influence on employee performance of XYZ’s Company. Through this research can provide input to the company’s management to maintain and manage the motivation, job satisfaction, and organizational support to make it better in order employees can increase attendance and can give better contribution on increase their performance at XYZ’s Company.